Revisiting the economic growth and electricity consumption nexus in Pakistan - Balcilar, Mehmet; Bekun, Festus Victor; Uzuner, Gizem (Springer Heidelberg, 2019)
This paper revisits the interaction between electricity consumption, real gross domestic product, and carbon dioxide emissions in Pakistan. To this end, our study relies on annual data from 1971 to 2014 for the econometric analysis while accounting for structural break(s). According to the Maki cointegration test, a cointegration equilibrium relationship exists among electricity consumption, economic growth, and carbon dioxide emissions. The empirical findings from Toda-Yamamoto causality test provided the following insights: (i) unidirectional causality was found running from economic growth to electricity consumption. Thus, this study validates the conservative hypothesis, meaning that in Pakistan, conservative energy strategies cannot harm economic progress. (ii) Causality was also found running from electricity consumption to carbon dioxide emissions. This implies that industrial activities trigger an increase in carbon emissions flaring which in return translates into environmental degradation. This outcome has inherent policy implications which are further discussed in the conclusion section.
Keywords: Electricity consumption; Economic growth; Maki cointegration; Pakistan; C32; O41; Q43